Editorial Preface - Ibrahim, Nabilah; Ismail, Al Emran; Daud, Zawawi (International Journal of Integrated Engineering, 2018)
This special issue of International Journal of Integrated Engineering provides deep research on Future Technology Towards a Smart and Healthy Society, contains 30 papers contributions by more than 50 authors from various institutions. This special appreciation goes to all Editorial Team members and also Guest Editorial Team members for the evaluation process with strict comments to improve the quality of the content. Generally, the area covered in this special issue is focus on future technology by proposing numbers of novel techniques especially health monitoring system, health assessment and power system techniques towards clean and better society including weather classification method. The goal of this special issue is to present and provide platform of various engineering field results, thus it is believed that the papers will be the good references and bring directions to researchers in their research discipline.